Estudo tecnológico em rejeitos de quartzitos do sudoeste de Minas Gerais para utilização como agregado graúdo no concreto - Francklin Junior, Ivan (2009)
The Southwest of the Brazilian State of Minas Gerais is nationally known by the production of quartzite used as floor and wall covering. The extraction of the quartzite in the region, even when obey the determinations of the ambient agencies, generates a great amount of waste. The waste generated in the extraction and processing of the slates is an enormous problem for the society. The objective of this research is to characterize the quartzite waste to verify the possibility of its use as concrete coarse aggregate. The work concerned the definition of the places and the collect of the samples, samples petrographic appreciation, production of aggregates, samples technological characterization and confection of the concrete in laboratory. The results obtained in the technological characterization of the quartzite samples and of the concrete had been satisfactory, with exceptions in the elongated and flaky fragments by use of the jaw crusher for processing and of the potential deleterious reactivity of the quartzite with the alkalies in the cement CP II-Z-32 and CP V.